Towards a representation for multi–viewpoints ontology alignments. (11th April 2014) - Djakhdjakha, Lynda; Hemam, Mounir; Boufaïda, Zizette
In a heterogeneous multi–communities organisation, several communities or groups of users exist with their own viewpoints. Multi–viewpoint ontologies are becoming a crucial aspect in overcoming the limitations of sharing knowledge and keeping the viewpoint of each member of the community. Various ontology alignment approaches have been proposed; however, no system has explored the problem of ontology alignment in the specific context of multi–viewpoints. Moreover, the proposed alignment formats are not sufficient to cover the representation needs of the multi–viewpoints ontology alignments. The key insight into this work is that multi–viewpoints alignment is a set of semantic correspondences between multi–viewpoints ontology elements. Thus, this work focuses on the proposition of a new format allowing the presentation of semantic mapping between multi–viewpoints ontology elements. The extended multi–viewpoints alignment format has the possibility to take into account the different viewpoints' aspects in formal way.